2022
DOI: 10.55048/jpns.v1i3.52
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitudes, and willingness of pre-clinical nursing students to provide nursing care for people living with HIV/AIDS

Abstract: Background: HIV/AIDS as a global pandemic forced the nursing student to have appropriate knowledge and attitudes toward caring for people living with HIV/AIDS (PLWHA).  Purpose: This study aims to explore the level of knowledge, attitudes, and willingness of pre-clinical nursing students to provide nursing care for PLWHA. Methods: A descriptive and cross-sectional study is conducted. A total of 185 pre-clinical nursing students enrolled in Bachelor of Science in Nursing (BSN), and Associate Degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Sebagai retrovirus, virus ini dapat menginfeksi tubuh dalam jangka waktu yang lama. Penyakit HIV/AIDS telah berkembang menjadi pandemi di berbagai negara tersebut dan memiliki dampak yang signifikan terhadap ekonomi global (Chaudhary et al, 2016) (Chanvatanak et al, 2022).…”
Section: Latar Belakangunclassified
“…Sebagai retrovirus, virus ini dapat menginfeksi tubuh dalam jangka waktu yang lama. Penyakit HIV/AIDS telah berkembang menjadi pandemi di berbagai negara tersebut dan memiliki dampak yang signifikan terhadap ekonomi global (Chaudhary et al, 2016) (Chanvatanak et al, 2022).…”
Section: Latar Belakangunclassified
“…Internationally, studies have revealed that seminar and virtual patient simulation activity focusing on PLWHAs can positively impact nursing students' attitudes [ 13 , 14 ]. Although nursing education programs have made great efforts over the past decade, and the proportion of healthcare providers unwilling to take care of patients with AIDS has declined, nursing practitioners still feel fear and tend to keep a distance from PLWHAs [ 15 , 16 ]. The underlying reasons why HIV and AIDS care occurs in the context of unfavorable nursing attitudes deserve to be futher explored.…”
Section: Introductionmentioning
confidence: 99%